2022
DOI: 10.3389/fgene.2022.824739
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Electroacupuncture at Zusanli (ST36) on Intestinal Microbiota in Rats With Chronic Atrophic Gastritis

Abstract: Background: Electroacupuncture is a common treatment for chronic atrophic gastritis (CAG) in China. We aimed to determine the effects of electroacupuncture at zusanli (ST36) on intestinal microbiota in CAG rats.Methods: In total, 42 SD rats were randomly divided into normal (NC, 10 rats) and model (MG, 32 rats) groups. Rats in the MG group were established as CAG disease models. After that, the rats in the MG group were randomly divided into CAG (10 rats), electroacupuncture (EA, 10 rats), and Vitacoenzyme (Vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(29 citation statements)
references
References 37 publications
0
26
0
Order By: Relevance
“…Zhou et al ( 2020 ) observed that the bacterial Blautia decreased in gastritis subjects. Huang et al's ( 2022 ) team found that the abundance of bacteria Blautia decreased in CAG patients. These studies have shown the beneficial effects of the bacteria on health.…”
Section: Discussionmentioning
confidence: 99%
“…Zhou et al ( 2020 ) observed that the bacterial Blautia decreased in gastritis subjects. Huang et al's ( 2022 ) team found that the abundance of bacteria Blautia decreased in CAG patients. These studies have shown the beneficial effects of the bacteria on health.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, the Bacteroides pectinophilus group increased after ZEN exposure in both fractions, a taxon that is hardly described in rumen research. When very cautiously extrapolating intestinal microbiota data from rodents, the Bacteroides pectinophilus group could be an indicator of a disturbed microbial community in the gut [ 15 ], but the need for further clarification on the role of this microbial group during mycotoxin exposure in the rumen is explicitly emphasized. In contrast, the Z20 cluster belonging to Oligosphaeraceae declined in response to ZEN, a bacterial group that is also marginally recognized in rumen research but seems to react sensitively against this mycotoxin.…”
Section: Discussionmentioning
confidence: 99%
“…Oscillospirales was believed to produce short-chain fatty acids, and the level of it was also found to be decreased in disease ( 52 ). The Christensenellaceae has been found in human bodies, which plays an important role in human health ( 53 ).…”
Section: Discussionmentioning
confidence: 99%